Assessment of different shielding materials for radiation therapy of maxillofacial tumors - An in vitro study - K Kasim Mohamed; K Satish Srinivas; Madhankumar Seenivasan; Annapoorani Babu (Wolters Kluwer Medknow Publications, 2024)
Aim: Since the advent of radiotherapy, the success rate of head and neck cancer treatment has increased significantly. However, when the tissue tolerance level is exceeded, unnecessary and uncontrolled exposure to radiation is considered detrimental. Such problems remain difficult to prevent and manage. The aim of the study to evaluate and compare the degree of attenuation of therapeutic radiation using four different radiation shielding materials of varying thickness. Study Setting and Design: In vitro experimental study. Materials and Methods: The samples were divided into four groups based on the different radiation shielding materials of thickness 3mm and 5mm. The materials are Lead (Pb), Silver-tin alloy (Ag-Sn) with Polyvinylsiloxane (PVS), Polymethylmethacrylate (PMMA) with Barium sulphate (BaSO4), and a combination of Ag-Sn with PVS and PMMA with BaSO4 which was exposed to radiation. The radiation dose measurements were recorded and the radiation attenuation properties of the shielding materials were evaluated. Among all of the shielding materials the most efficient material under consideration is determined. Statistical Analysis Used: One-way ANOVA followed by post hoc test was used to compare the means of all four groups. Results: A statistically significant difference between groups was found by a one-way ANOVA with a P = 0.001. In the post hoc test, statistically significant findings were obtained with a P = 0.05 when comparing the variation values of 3mm and 5mm thickness between each group and other groups. Conclusion: The shielding materials results in significant reductions in radiation dosage. It was concluded that the combinations of Ag-Sn alloy with PVS, and PMMA with BaSO4 of thickness 5 mm had a good shielding effect.